An Approach to Improve the Quality of OFDM Signal Using Papr Reduction Schemes - Padaganur, Satyanarayan K; Mallapur, Jayashree D; Deshmukh, M N; Patil, P S (International Journal of Computer Sciences and Engineering, 2025)
Orthogonal-frequency division-multiplexing(OFDM) is a standout amongst many commended different access framework, which is capable of performing both modulation and multiplexing in both wired and wireless communication specially used to achieve the today‟s need of high speed communication beyond 4g-Long term evolution. OFDM was originally adapted by 3GPP association for the development of LTE. It has many advantageous characteristics such as higher spectral efficiency, higher bit rate, and lower multipath distortion etc. Even with these many advantages OFDM still suffers from few critical issues. One among them is OFDM signal‟s higher peak power ratio (PAPR). Which drives power amplifier into a nonlinear region hence results toout of band radiation and in band distortion which is a reason for degradation of performanceof the system in terms ofBER. Here we will demonstrate the reenactment of the OFDM with various supporting adjustment systems, for example: QPSK, QAM. Additionally, here will demonstrate an endeavor to decrease the PAPR utilizing distinctive PAPR lessening procedures to enhance the nature of the OFDM signal along withsimulation results.